Calculus : One and Several Variables - Salas, Saturnino L.; Hille, Einar; Etgen, Garret J. (John Wiley & Sons Singapore Pte. Ltd., 2021)
For ten editions, readers have turned to Salas to learn the difficult concepts of calculus without sacrificing rigor. Wiley is proud to publish a new revision of Calculus: One and Several Variables 10th Edition, known for its elegant writing style, precision and perfect balance of theory and applications. The Tenth Edition is refined to offer students an even clearer understanding of calculus and insight into mathematics. It includes a wealth of rich problem sets which makes calculus relevant for students. Salas/Hille/Etgen is recognized for its mathematical integrity, accuracy, and clarity that will help readers master these concepts and understand their relevance to the real world